ANALISIS TARAF HIDUP NELAYAN TRADISIONAL DI KECAMATAN BELANG KABUPATEN MINAHASA TENGGARA - Laside, Iftitah Khairunnisa Dg; Suhaeni, Siti; Luasunaung, Alfret; Darwisito, Suria; Mentang, Feny; Sumilat, Deiske A. (AKULTURASI, 2022)
Abstract The purposive of this study, namely to find out how much and what are the sources of income for traditional fishermen’s families in Belang District, and the expenses of traditional fishermen’s families in Belang District is, te last step is to find out how the standard of living of traditional fishermen’s families in Belang District is. The Method used in this research is a survey method. The population in this study are traditional fishermen in Belang District. The data collection method used is Sampling. The sampling method is using a quataed Multi-Stages Purposive Sampling, with the number of sample villages being 15 villages and the sample fishermen taken are fishermen with fishing rods and nets as much as 10% of the total population in each sample village. The data collected consists of primary data dan secondary data. Primary data was collected through observation and interviews guided by questionnaires. Secondary data were obtained from the Belang District of office and related to this research. The data analysis used is descriptive qualitative dan quantitative analysis. The standard of living of traditional fishing families is analyzed using the Engel index. Based on the results of the analysis, it is known that the income of traditional fishermen’s families in Belang District comes from their main job as fishermen, side jobs outside the field of fisheries. The total incomes of traditional fishermen’s families in Belang District on average for one year is Rp. 53.394.000. There are 2 types of expenditures for traditional fishermen’s families in Belang District, namely expenditures for food and expenditures for non-food such as clothing, housing, health, education, electricity, transportation and others. The total average expenditure for one year is Rp. 53.394.000, which is divided into expenditures for food needs of Rp. 32.284.500 and expenditures for non-food needs which are Rp. 21.109.500. The results of the analysis of the Engel index are 60,46%, meaning that the total income of traditional fishermen in Belang District is 60,46% used to meet food needs only. The proportion for food, which is 39,54%. This is indicating that the standard of living of traditional fishermen in Belang District is still relatively low because more than half of their income is only sufficient to meet food needs. Keywords: standard of living; traditional fishermen; Belang Abstrak Tujuan penelitian ini, yaitu untuk mengetahui berapa dan apa saja sumber pendapatan keluarga nelayan tradisional di Kecamatan Belang, dan pengeluaran keluarga nelayan tradisional di Kecamatan Belang. terakhir untuk mengetahui bagaimana taraf hidup nelayan tradisional di Kecamatan Belang. Metode yang digunakan dalam penelitian ini adalah metode survei. Populasi dalam penelitian ini adalah nelayan tradisional yang ada di Kecamatan Belang. Metode pengambilan data yang dilakukan adalah Sampling. Cara pengambilan sampel menggunakan Multi-Stages Purposive Sampling yang terkuota, dengan jumlah desa sampel adalah 15 desa dan nelayan sampel yang diambil adalah nelayan dengan alat tangkap pancing dan jaring sebanyak 10% dari total populasi yang ada pada setiap desa sampel. Data yang dikumpulkan terdiri atas data primer dan data sekunder. Pengumpulan data primer dilakukan melalui observasi dan wawancara yang dipandu dengan kuisioner. Data sekunder diperoleh dari kantor Kecamatan Belang dan penelitian-penelitian yang terdahulu yang ada kaitannya dengan penelitian ini. Analisis data yang digunakan adalah analisis deskriptif kualitatif dan kuantitatif. Taraf hidup keluarga nelayan tradisional di analisis dengan indeks Engel. Berdasarkan hasil analisis diketahui bahwa pendapatan keluarga nelayan tradisional di Kecamatan Belang bersumber dari pekerjaan pokok sebagai nelayan dan pekerjaan sampingan. Total pendapatan keluarga nelayan tradisional di Kecamatan Belang rata-rata per tahun adalah Rp. 53.394.000. Pengeluaran keluarga nelayan tradisional di Kecamatan Belang ada 2 macam, yaitu pengeluaran untuk pangan dan pengeluaran untuk non pangan seperti, pakaian, perumahan, kesehatan, pendidikan, listrik, transportasi, pulsa dan lain-lain. Total pengeluaran rata-rata per tahun adalah sebesar Rp. 53.394.000 yang terbagi menjadi pengeluaran untuk kebutuhan pangan sebesar Rp. 32.284.500 dan pengeluaran untuk kebutuhan non pangan yaitu sebesar Rp. 21.109.500 Hasil analisis Indeks Engel adalah 60,46%, artinya total pendapatan nelayan tradisional di Kecamatan Belang 60,46% digunakan untuk memenuhi kebutuhan pangan saja. Proporsi untuk pangan yaitu 60,46% jauh lebih besar dibanding proporsi untuk non pangan yaitu 39,54%. Hal ini menandakan bahwa taraf hidup nelayan tradisional di Kecamatan Belang masih tergolong rendah karena lebih dari separuh pendapatannya hanya cukup untuk memenuhi kebutuhan pangan saja. Kata Kunci: taraf hidup; nelayan tradisional; Belang